Hubungan Dukungan Suami dengan Kecemasan Ibu Hamil Trimester III di Puskesmas Tempel II Sleman Yogyakarta - chindy, chindy Oktavi Harto; Sulistyoningtyas, Sholaikhah (Jurnal Sains & Kesehatan, 2024)
Pregnancy is generally regarded as a joyful experience for women, although it can also elicit anxiety due to the potential risks and issues that may arise for both the mother and fetus. One effective strategy to alleviate such anxiety is through the provision of support from the spouse, which manifests as attentive and affectionate care. Both physical and psychological support can be offered to individuals. The attitude of husbands plays a significant role in influencing the health state of the mother. Good husband support can provide good motivation for mothers to check their pregnancy. Objective: This study aims to determine the correlation between husband support and anxiety of third trimester pregnant women at Puskesmas (primary health center) Tempel II Sleman Yogyakarta. The research was quantitative study using the Correlation Descriptive method with a Cros Sectional approach. The population in this study were Trimester III pregnant women in the working area of Puskesmas Tempel II Sleman Yogyakarta. The sampling in this study used Purposive Sampling technique. Data analysis used Fisher's Exact Test. The results of the analysis with Fisher's Exact Test test obtained bivariate results meaning there was a significant correlation between husband support with anxiety of third trimester pregnant women with a value (P.value 0.002 < a = 0.05). The results of this study indicate that there exists a moderate association between the level of support provided by husbands and the anxiety experienced by pregnant women in their third trimester. Suggestion: It is recommended that the midwives at Puskesmas Tempel II Sleman Yogyakarta be equipped to offer comprehensive information regarding examination outcomes and provide guidance to spouses in the event that patients encounter difficulties, particularly addressing the anxiety experienced by pregnant women in their third trimester.